2018
DOI: 10.1017/wsc.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of Five Palmer amaranth (Amaranthus palmeri) Populations Grown in Northern Indiana and Arkansas

Abstract: Palmer amaranth (Amaranthus palmeriS. Watson) is a problematic weed encountered in U.S. cotton (Gossypium hirsutumL.) and soybean [Glycine max(L.) Merr.] production, with infestations spreading northward. This research investigated the influence of planting date (early, mid-, and late season) and population (AR, IN, MO, MS, NE, and TN) onA. palmerigrowth and reproduction at two locations. All populations planted early or midseason at Throckmorton Purdue Agricultural Center (TPAC) and Arkansas Agriculture Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…No significant differences were observed between populations of both weeds in plant height, number of leaves and biomass. In contrast, Spaunhorst et al 30 observed different growth and seed production between Amaranthus palmeri S. Watson populations in response to different planting www.nature.com/scientificreports/ dates. Different responses in weed populations to environmental factors can be attributed to genetic diversity and maternal conditions over the course of maturation 44,45 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…No significant differences were observed between populations of both weeds in plant height, number of leaves and biomass. In contrast, Spaunhorst et al 30 observed different growth and seed production between Amaranthus palmeri S. Watson populations in response to different planting www.nature.com/scientificreports/ dates. Different responses in weed populations to environmental factors can be attributed to genetic diversity and maternal conditions over the course of maturation 44,45 .…”
Section: Discussionmentioning
confidence: 89%
“…It could be concluded that, that, despite the reduction in the number of seeds in late-emerged weeds, the control of these weeds (even in boundary areas) should not be neglected in order to achieve sustainable and long-term weed management. In the current study, the viability and dormancy of produced seeds-which play an important role in the proliferation of weeds-from different planting dates were not evaluated 30,39,50 . Furthermore, it has been reported that the interaction effects of flowering time and growth period length could result in different emergence responses to environmental conditions as observed in the collected seeds of Ipomoea hederacea (L.) Jacq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential effect of fomesafen may be due to the presence of the adjuvant system in the Flexstar ® herbicide, which increases herbicide absorption and translocation. A priority for early season control of A. palmeri could also be beneficial as late emerging populations have been observed to be more male-biased than early season populations [64]. Populations with a female-biased sex ratio may need more effective management practices than populations having more male-biased sex ratios where fewer seeds will be produced.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, information on weed phenology would allow more specific control methods to be developed by accurately estimating the timing and effects of weed competition on crop yield (Ghersa and Holt, 1995). A recent study on Amaranthus palmeri S. Watson phenology concluded that while species originating from different regions of the USA can vary biologically, it was the plant's environmental plasticity which contributed to population spread (Spaunhorst et al, 2018).…”
Section: Weed Biology and Ecologymentioning
confidence: 99%